(3TQM GdeLSWi (B( (3aj GdgjFI (B)s - (3CHh Ydj eMeO Hf GdMSf Hf GdgjKes; (3HWdjehS GdMcje GdbdhPjs ((3GdbGgQI s)
(3ChdgG (B:s
(3bGd GdYde ef LgI MOg gh GdJjbf GdYbdi GdeOQc dMbGFb GdCTjGA hCaVd eYGfi GdJYGdje eG JVefg cJGH HWdjehS GdeJQLe HGdeLSWi s
(3BNQgG (B:s
(3aEfg jJMUd HPdc GdELJeGYGJ hGdESJbHGdGJ Ydi GdJhGdi ef Chd GdSfI Edi CNQgG eWdbI heMOOI hgPg gi GdLOGhd aQZJ ef JYdjb s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3cJHJ Hbde eged GdfbW CMjGfkGs
(3fbdJ ef fSNI SbjeI HgG CTcGds
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B431 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
Keywords: (3Gdadcs